Impact of a psychoeducational nursing program on self-efficacy and psychological adjustment in hemodialysis patients - Basmah Abdel-Nasser Helali; Sahar Mahmoud Eliwa; Fatma Ata Abd El-Salihen Nosir; Shimaa Saied Adam Mohamed (Scientific Reports)
Abstract Self-efficacy and psychological adjustment to illness are crucial for new hemodialysis patients as they empower individuals to manage their treatment effectively and cope with the emotional and physical challenges of their condition. Research on the psychological aspects of hemodialysis patients in the Middle East is limited, and even rarer are interventions specifically tailored to promote them. This study evaluates the impact of a psychoeducational nursing program on self-efficacy and psychological adjustment among hemodialysis patients. A quasi-experimental design was utilized with a purposive sample of 53 patients aged 18–60 years, undergoing hemodialysis for less than a year at NIUN, Cairo, Egypt. Data were collected using a socio-demographic and clinical data questionnaire, Self-Efficacy for Hemodialysis Scale, and Psychological Adjustment to Illness Scale. Our program, which specifically targeted new hemodialysis patients, aimed to facilitate faster and more effective psychological adaptation through interactive discussions, practical coping strategies, and educational materials on disease management and self-care. Our study showed improvement in self-efficacy for hemodialysis patients in pre- and post-program implementation, with a p-value of (0.057), and a highly significant improvement in psychological adjustment to illness, with a p-value of (0.001). Based on the improvements observed, psychoeducational programs should be integrated into standard care for new hemodialysis patients, with a focus on multidisciplinary collaboration to address both medical and psychological needs.